A new species of Neoderus Alexander, 1927 (Diptera: Tanyderidae) from southern Chile, with a first description of a male and key to extant genera of the family. Issue 2 (3rd July 2018) - Isaí Madriz, R.; Astorga, Anna; Lindsay, Targe; Courtney, Gregory W.
ABSTRACT: Neoderus Alexander, 1927 (Diptera: Tanyderidae) is revised to include a new species, Neoderus chonos Madriz, sp. n. Adults of N. chonos were collected in January 2016 from two sites in Chilean Patagonia. This paper provides a description of the new species, including the first male description of the genus, diagnosis of adult Neoderus, and redescription of N. patagonicus (Alexander, 1913). Habitat characteristics, known distribution and historical information for the new species are also discussed. A generic key to adults of world Tanyderidae is given. urn:lsid:zoobank.org:pub:27F176EE-57EE-4427-BD97-521FA4C92D68